2018
DOI: 10.1021/acs.jpclett.8b00921
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Photoprotection Properties of Mycosporine Amino Acid Motifs

Abstract: Photoprotection from harmful ultraviolet (UV) radiation exposure is a key problem in modern society. Mycosporine-like amino acids found in fungi, cyanobacteria, macroalgae, phytoplankton, and animals are already presenting a promising form of natural photoprotection in sunscreen formulations. Using time-resolved transient electronic absorption spectroscopy and guided by complementary ab initio calculations, we help to unravel how the core structures of these molecules perform under UV irradiation. Through such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 33 publications
12
68
0
Order By: Relevance
“…[59][60][61] This may imply that further modification of the core unit makes the S1/S0 CI energy accessible to excited state population, possibly through additional substitution to differing ring positions ( Figure 6 The authors close by placing their research in the wider field of natural sunscreens highlighting that their results strongly favour the use of both shinorine and porphyra-334 in an in-vivo environment as natural sunscreen filters, even though a small proportion of the excess energy remains trapped as a triplet population with a significantly longer lifetime. 62,63,65 Relating this work to Case Studies 1 and 2, the proposed overall dynamics of the system agree with those of the MAA-inspired systems by Losantos et al and Woolley et al: 16,27 rapid relaxation through an accessible CI resulting in a vibrationally excited electronic ground state.…”
Section: Case Studiessupporting
confidence: 81%
“…[59][60][61] This may imply that further modification of the core unit makes the S1/S0 CI energy accessible to excited state population, possibly through additional substitution to differing ring positions ( Figure 6 The authors close by placing their research in the wider field of natural sunscreens highlighting that their results strongly favour the use of both shinorine and porphyra-334 in an in-vivo environment as natural sunscreen filters, even though a small proportion of the excess energy remains trapped as a triplet population with a significantly longer lifetime. 62,63,65 Relating this work to Case Studies 1 and 2, the proposed overall dynamics of the system agree with those of the MAA-inspired systems by Losantos et al and Woolley et al: 16,27 rapid relaxation through an accessible CI resulting in a vibrationally excited electronic ground state.…”
Section: Case Studiessupporting
confidence: 81%
“…Probe pulses are held at 54.7°relative to the pump-pulses and are delayed after pump photoexcitation up to a maximum of 2 ns, through the use of a hollow gold retroreflector in the path of the probe beam. [2,31] SdiEM and SdiTBM were investigated using an identical procedure. The collected transient absorption spectra (TAS) are chirp corrected and analysed through the use of a global fitting procedure provided in the Glotaran package, [32] using a sequential kinetic model.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Carbon three is substituted with an amino group (represented as R in Figure 10 ), and this is what causes the variability among mycosporines [ 60 ]. We begin the mycosporine discussion by reviewing work conducted by Losantos et al [ 89 ] and Woolley et al [ 85 ] on basic cyclohexenone structures, herein referred to as mycosporine motifs. Further details of these authors’ works can be found in the reviews by Holt and Stavros [ 55 ] and Woolley and Stavros [ 83 ].…”
Section: Case Studiesmentioning
confidence: 99%
“…Further details on the methodology, such as the active space and basis set used, can be found in the original research [ 89 ], as is the case with all the theoretical work reviewed in Section 2 . Woolley et al [ 85 ] studied a modification of molecule 2, 3-aminocyclohex-2-ene-1-one (termed ACyO, the methyl group on the nitrogen attached to carbon three in molecule 2 is replaced with a hydrogen), experimentally using TEAS along with complementary computational studies; see Figure 10 . All four mycosporine motifs are composed of the same cyclohexenone core structure, with varying substituents on carbons two and three.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation